Nonenzymatic glycosylation in vitro and in bovine endothelial cells alters basic fibroblast growth factor activity. A model for intracellular glycosylation in diabetes. - Giardino, I (1994)
Intracellular sugars are more reactive glycosylating agents than glucose. In vitro nonezymatic glycosylation of basic fibroblast growth factor (bFGF) by fructose, glucose-6-phosphate (G6P), or glyceraldehyde-3-phosphate (G3P) reduced high affinity heparin-binding activity of recombinant bFGF by 73, 77, and 89%, respectively. Mitogenic activity was reduced 40, 50, and 90%. To investigate the effects of bFGF glycosylation in GM7373 endothelial cells, we first demonstrated that GLUT-1 transporters were not downregulated by increased glucose concentration. In 30 mM glucose, the rate of glucose transport increased 11.6-fold, and the intracellular glucose concentration increased sixfold at 24 h and fivefold at 168 h. The level of total cytosolic protein modified by advanced glycosylation end-products (AGEs) was increased 13.8-fold at 168 h. Under these conditions, mitogenic activity of endothelial cell cytosol was reduced 70%. Anti-bFGF antibody completely neutralized the mitogenic activity at both 5 and 30 nM glucose, demonstrating that all the mitogenic activity was due to bFGF. Immunoblotting and ELISA showed that 30 mM glucose did not decrease detectable bFGF protein, suggesting that the marked decrease in bFGF mitogenic activity resulted from posttranslational modification of bFGF induced by elevated glucose concentration. Cytosolic AGE-bFGF was increased 6.1-fold at 168 h. These data are consistent with the hypothesis that nonenzymatic glycosylation of intracellular protein alters vascular cell function.